Lights up when plugged in, the superpower of disability: an arts-based narrative - Crawford, Betsy Lou (Kansas State University, 2017)
The purpose of this case study was to explore how two people with language-based learning disabilities, who have graduated from Masters of Fine Arts Master’s (MFA) programs describe their coping mechanisms, career aspirations, and identity development as a result of being involved in the creative arts. This qualitative study was conducted with purposeful and criterion-based sampling. The participants must have graduated from a MFA program with a focus on a studio art and have a language-based learning disability. Arts-based narrative inquiry research was used to explore the manner in which each participant negotiated their path through multiple educational settings from K-12 to a terminal master’s degree. The participants’ narratives were articulated using a Bildungsroman format to share their coming of age story as their identities developed. Findings indicate the participants with language-based learning disabilities used multiple coping mechanisms to negotiate their path through the education settings they encountered as they grew into adults and completed terminal MFA degrees. They relied on extra time, isolation, help from others, and their creativity in an attempt to hide their language-based learning disabilities. The study raised implications about the amount of support students with learning disabilities have at each level of education. It also raised questions about what help students with disabilities need for long term success as they transition from one level of education to the next, this includes mental health support.
Keywords: Bildung; Arts-based research; Special education; Narrative inquiry; Language-based learning disablity